Students' Difficulties In Solve Trigonometry Problem Solving According To Step Polya's - Khofifah, Khofifah; Rosyadi, Rosyadi; Gunadi, Farid; Nandang, Nandang; Runisah, Runisah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to describe students' difficulties in solve trigonometry problem solving according Polya's steps. Determining research subjects by giving students difficulty test questions using Polya steps to 36 students of class X MIPA 8 SMAN 1 Indramayu. From these results, 6 subjects were selected purposively as a sample with subjects falling into the high, medium and low score categories. The instruments used were diagnostic tests of students' difficulties in solving trigonometric problems using Polya's problem solving and interviews. The data analyzing technic in the research started with collecting information in the fields, interviews, and documentations which are collected by coding. By considering into account the results obtained from this study, the difficulty of students in handling problem solving of trigonometry problems according to Polya's steps owned by students of class X MIPA 8 SMA Negeri 1 Indramayu is able to solve a problem using Polya's steps. When students who have high test scores will have little difficulty learning because the subject can explain and solve problems well and there are no difficulties. While it is different when students who have low scores feel confused, difficult, wrong in solving a problem. In fact, in this study, the highest score and the lowest score both answered the questions correctly, the only difference was the student's accuracy and overestimation, causing the student to get a low score. The research results show that the students with high score category had less difficulty than students with low score categories. Therefore, teachers must be more careful in paying attention to students and teachers must also explain Polya's stages gradually without rushing. It is expected that students can understand Polya's stages as a whole so as to reduce student learning difficulties.